Peran Perempuan dalam Novel Cinencang Lawe Karya Tulus Setiyadi Kajian Feminisme - Kusuma, Shella Nada; Werdiningsih, Yuli Kurniati; Sunarya, Sunarya (Universitas PGRI Semarang, 2021)
The purpose of writing this article is to describe the role of women experienced by characters in Tulus Setiyadi novel Cinencang Lawe. As the author, Tulus Setiyadi describes the role of women in the novel Cinencang Lawe. The method used in this writing is qualitative research. The research data is in the form of words, phrases, sentences, and discourses which contain elements regarding the role of women. The theory used is feminism with a focus on the role of women and their efforts in dealing with problems. The techniques used in this research are reading and note taking techniques. The results of this study are there are two roles of women in each character in the novel Cinencang Lawe, namely the domestic role in the household and the public role in society and the social sphere as described Darmini, Lik Wiji, Mbok Yem,Â Juragan Lamini dan Ibu Narji.